CDNA expression library screening revealed novel functional genes involved in clear cell carcinogenesis of the ovary in vitro. (2nd January 2021) - Yamada, Yasushi; Miyamoto, Tsutomu; Higuchi, Shotaro; Ono, Motoki; Kobara, Hisanori; Asaka, Ryoichi; Ando, Hirofumi; Suzuki, Akihisa; Shiozawa, Tanri
Abstract: In order to identify genes involved in the pathogenesis of clear cell carcinoma of the ovary (CCC), functional screening using a cDNA expression library was performed. We extracted mRNA from a CCC cell line (RMG-1), established a cDNA library using a retroviral vector, transfected that library into mouse NIH3T3 cells and sequenced the resultant foci. The tissue-type specific expression of isolated genes and their transforming activities were evaluated. Seven genes were isolated. Of these genes, the mRNA expression of SEC61B and DVL1 is significantly stronger in CCC than in other histological types ( p  < .05). Immunohistochemical staining reveals the stronger expression of SEC61B and C1ORF38 than normal ovarian tissues ( p  < .05). Focus formation is confirmed by the transfection of SEC61B, C1ORF38, and DVL1 into NIH3T3 cells. The present study identified novel genes including SEC61B, C1ORF38, and DVL1, involved in the pathogenesis of CCC. These genes may be additional therapeutic targets for CCC. Impact statement: What is already known on this subject? Several important genetic abnormalities, including ARID1A and PIK3CA mutations, have been reported in ovarian clear cell carcinoma (CCC). What the results of this study add? SEC61B, C1ORF38, and DVL1 were newly detected as candidate genes involved in ovarian clear cell carcinogenesis. What the implications are of these findings for clinical practice and/or further research? Functional screening using a cDNA expression library may be a useful technique to identify functional genes for pathogenesis. The information obtained using this technique may provide new therapeutic targets of CCC.